Self-perception of PsyCap in Higher Education Program Coordinators - Silva, Andréia Bonato da (2018)
This study analyzes the self-perception of higher education program coordinators working on private and community higher education institutions in Southern Brazil about their Psychological Capital (PsyCap), and their perceived ability to generate PsyCap in faculty members with whom they work. The study is based on four dimensions to assess PsyCap: Optimism, Self-Efficacy, Hope and Resilience (Luthans, Youssef, & Avolio, 2007; Luthans, Youssef-Morgan, & Avolio, 2015), and some references on University Management, focusing on the role of program coordinators (Argenta, 2011; Colombo, 2011, 2013; Demo, 2005; Ferreira, 2009; Franco, 2013; Marcon, 2008). The research design is mixed, with data gathered by an electronic survey based on the Psychological Capital Questionnaire (PCQ24) instrument (N = 309), followed by semi-structured interviews with 10 program coordinators. Data analyses indicate a considerable amount of operational activities assigned to program coordinators, which interferes in their capacity of fully manage the programs they coordinate. Average level of Self-Efficacy was higher in men, and average level of Optimism was higher in women. The years of working experience at University was significant to self-perceived PsyCap levels, and coordinators who have between 5 and 10 years of working experience in higher education institutions presented the higher average of self-perceived PsyCap in the sample.